2010
DOI: 10.1111/j.1464-5491.2010.03068.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting improved glycaemic control in youth using insulin pumps

Abstract: This study emphasizes the importance of blood glucose testing, of bolus insulin administration and of an increase in the time of temporary basal rate use in relation to improving glycaemic control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
31
4
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 10 publications
7
31
4
2
Order By: Relevance
“…Likewise, Shalitin et al showed that only toddlers continued to decrease the HbA 1c level even after three years [8]. We found that age showed a significant negative correlation with the daily number of boluses and SMBG's in accordance with Wilkinson et al [25] (Table 3). Another finding was a significant difference in the amount of pubertal and prepubertal children among the responder and non-responders at 24 months follow-up.…”
Section: Discussionsupporting
confidence: 92%
“…Likewise, Shalitin et al showed that only toddlers continued to decrease the HbA 1c level even after three years [8]. We found that age showed a significant negative correlation with the daily number of boluses and SMBG's in accordance with Wilkinson et al [25] (Table 3). Another finding was a significant difference in the amount of pubertal and prepubertal children among the responder and non-responders at 24 months follow-up.…”
Section: Discussionsupporting
confidence: 92%
“…23 The use of other pump options such as the temporary basal rate also provides an improvement in HbA1c levels. 24 Seasonal switch to MDI concerned only 10% of our cohort. These switches were usually of 1-month duration and did not exceed 2 months, therefore explaining the lack of glucose control impairment associated with seasonal switch.…”
Section: Discussionmentioning
confidence: 99%
“…We recently evaluated factors related to improvement in hemoglobin A1c (HbA1c) levels in youth using an insulin pump. 11 The more frequent use of temporary basal rates was the number one factor relating to improvement in the HbA1c level. (Admittedly, this may just be a reflection of paying closer attention to the person's diabetes.)…”
Section: Temporary Basal Ratesmentioning
confidence: 99%